2019
DOI: 10.1177/1756286419876521
|View full text |Cite
|
Sign up to set email alerts
|

Do early prednisolone and other immunosuppressant therapies prevent generalization in ocular myasthenia gravis in Western populations: a systematic review and meta-analysis

Abstract: Background: The majority of ocular myasthenia gravis (OMG) patients will progress to generalized myasthenia gravis (GMG), usually within 2 years of disease onset. The aim of this meta-analysis was to evaluate the effect of early prednisolone and other immunosuppressants therapy on the generalization rate in OMG patients. Methods: We searched the CENTRAL, EMBASE, and MEDLINE databases via the Ovid SP database for all relevant publications on 16 July 2018. Results: Eight studies comprising a total of 547 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…We analyzed this parameter to understand if achieving the proposed treatment target is associated with a reduced risk for MC [ 17 ]. Treatment strategies were previously suggested to affect the course of disease in MG. As such, a recent meta-analysis suggested that cortisone treatment reduces the risk for secondary generalization for MG patients with ocular manifestation [ 28 ]. Thymectomy is also evidenced to improve clinical readouts over a 3-year time span as demonstrated in a recent, randomized, controlled trial [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed this parameter to understand if achieving the proposed treatment target is associated with a reduced risk for MC [ 17 ]. Treatment strategies were previously suggested to affect the course of disease in MG. As such, a recent meta-analysis suggested that cortisone treatment reduces the risk for secondary generalization for MG patients with ocular manifestation [ 28 ]. Thymectomy is also evidenced to improve clinical readouts over a 3-year time span as demonstrated in a recent, randomized, controlled trial [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several strengths. First, most previous studies included immunosuppressed patients, potentially affecting the reported outcomes [ 1 , 2 , 5 14 , 20 , 28 ], as immunosuppression may reduce the risk of generalization [ 3 , 4 ]. Excluding this patient group may increase study validity.…”
Section: Discussionmentioning
confidence: 99%
“…Early immunosuppression therapy with steroids and other non-steroidal immunosuppressants may prevent the progression to GMG [ 3 , 4 ]. However, not all patients will ultimately develop generalization, with approximately 20% of patients not progressing to generalized disease irrespective of immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The factors which are proposed to be associated with generalization are older age at onset, RNS abnormalities in facial nerve, AChR antibody positivity, less use of early immunosuppressive therapy, presence of thymoma, and shorter disease duration. [97][98][99][100] However, these studies were retrospective and the patients were treated with immunosuppressive agents, which might have confounded the association results due to their disease modifying effects. 74 Though a study to evaluate the risk factors in nonimmunosuppressed patients is required; it might not be ethically justified.…”
Section: Progression To Generalized Myasthenia Gravismentioning
confidence: 99%